Accuracy of administrative claims data to identify dose specific rotavirus vaccination information: Implications for studies of vaccine safety. Issue 22 (21st May 2015) - Quinlan, Scott C.; Lanes, Stephan; Holick, Crystal N.; Mast, T. Christopher
Abstract Background The accuracy of vaccine administration information recorded in administrative claims databases is uncertain. Methods We conducted a retrospective cohort study using the HealthCore Integrated Research DatabaseSM among infants who received at least 1 RotaTeq® (RV5) dose during the first year of life between February 1, 2006 and November 30, 2012 and were enrolled in the health plan at birth. We reviewed medical records for a sample of infants to validate vaccine administration information. Results We identified 169, 560 infants who received at least 1 RV5 dose. Medical records were obtained for 85 infants, of which 74 (PPV1 87.1%; 95% CI 78.0–93.4%) had a corresponding first RV5 vaccination in the medical record with the same or similar administration date. Conclusions Administrative claims contained inaccuracies in dose number or administration date for 13% of RV5 first doses identified.